2021
DOI: 10.1186/s12909-021-02871-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on teaching and learning in health professional education: a mixed methods study protocol

Abstract: Background Due to the complex nature of healthcare professionals’ roles and responsibilities, the education of this workforce is multifaceted and challenging. It relies on various sources of learning from teachers, peers, patients and may focus on Work Integrated Learning (WIL). The COVID-19 pandemic has impacted many of these learning opportunities especially those in large groups or involving in person interaction with peers and patients. Much of the curriculum has been adapted to an online f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 19 publications
(23 reference statements)
1
57
0
2
Order By: Relevance
“…Due to the pandemic, overnight: 1) clinical activities were suspended; 2) nursing faculties were compelled to transition to online education; and 3) students were required to adapt to a self-directed/self-regulated learning model ( Ramos-Morcillo et al, 2020 ). This transition inevitably impacted nursing students' continuity of learning, and faculty members' adaptation to new teaching pedagogies ( Kumar et al, 2021 ). As online education is growing in prevalence and is anticipated to persist post-COVID-19, considerable attention must be paid to understand the experiences of navigating online education.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the pandemic, overnight: 1) clinical activities were suspended; 2) nursing faculties were compelled to transition to online education; and 3) students were required to adapt to a self-directed/self-regulated learning model ( Ramos-Morcillo et al, 2020 ). This transition inevitably impacted nursing students' continuity of learning, and faculty members' adaptation to new teaching pedagogies ( Kumar et al, 2021 ). As online education is growing in prevalence and is anticipated to persist post-COVID-19, considerable attention must be paid to understand the experiences of navigating online education.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in technology and the accessibility of devices have facilitated the adoption of online education platforms ( Bdair, 2021 ). Through online education, faculty members can engage large cohorts of students concurrently with both synchronous and asynchronous learning options ( Kumar et al, 2021 ). The main advantages of online education include increased accessibility, affordability, comfort, ease of management and use, flexibility and remote delivery ( Dhawan, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be defined as instruction delivered on a digital device that is intended to support learning. 10 , 11 , 12 Interestingly the transition to online within the health sciences has been gradual. 13 In response to the pandemic, a university in Johannesburg announced that the academic calendar would resume online given the nature of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported is part of a larger project which evaluates longitudinally the impact of the change to teaching and learning approaches in selective health disciplines, including remote education and changes to work-integrated learning, during the COVID-19 pandemic ( 25 ). This study was underpinned by pragmatism, which suggests pluralistic approaches to address research questions ( 26 , 27 ).…”
Section: Methodsmentioning
confidence: 99%